A structural basis for kinetochore recruitment of the Ndc80 complex via two distinct centromere receptors. (18th January 2013) - Malvezzi, Francesca; Litos, Gabriele; Schleiffer, Alexander; Heuck, Alexander; Mechtler, Karl; Clausen, Tim; Westermann, Stefan
<x xml:space="preserve">Abstract</x> The Ndc80 complex is the key microtubule‐binding element of the kinetochore. In contrast to the well‐characterized interaction of Ndc80‐Nuf2 heads with microtubules, little is known about how the Spc24‐25 heterodimer connects to centromeric chromatin. Here, we present molecular details of Spc24‐25 in complex with the histone‐fold protein Cnn1/CENP‐T illustrating how this connection ultimately links microtubules to chromosomes. The conserved Ndc80 receptor motif of Cnn1 is bound as an α helix in a hydrophobic cleft at the interface between Spc24 and Spc25. Point mutations that disrupt the Ndc80–Cnn1 interaction also abrogate binding to the Mtw1 complex and are lethal in yeast. We identify a Cnn1‐related motif in the Dsn1 subunit of the Mtw1 complex, necessary for Ndc80 binding and essential for yeast growth. Replacing this region with the Cnn1 peptide restores viability demonstrating functionality of the Ndc80‐binding module in different molecular contexts. Finally, phosphorylation of the Cnn1 N‐terminus coordinates the binding of the two competing Ndc80 interaction partners. Together, our data provide structural insights into the modular binding mechanism of the Ndc80 complex to its centromere recruiters.